Educational visit to Bank Pembangunan Malaysia Berhad: a valuable learning experience - Mejri, Norazimah (Corporate Communication Unit, UiTM Mukah Campus, 2025)
During the visit, students were given presentations by senior officers who shared insights into the bank’s operations, financial instruments, and risk management strategies. One of the highlights was a session on BPMB’s Sustainable Development Financing, which integrates environmental, social, and governance (ESG) principles into project evaluation, an essential trend in modern finance.